The Study of The Type Laboratory Examination in Health Service Facilities With Integration Determination of Local Content Courses DIII-Health Analyst - Purjanto, Kuntjoro Adi; Widiyanto, S.Y Didik; Budiharjo, Teguh (Jaringan Laboratorium Medis, 2019)
Introduction: Health Laboratory Services is an integral part of healthcare services to the public. The main task of health analyst conducts healthcare laboratory services. In order to produce health analyst personnel who meet the needs of graduates or stake holders, the education will apply the curriculum for the learning process. Diploma in Education 3 students must take at least 108 credits (semester credit unit). Meanwhile, the education core Curriculum 3 medical laboratory technology defined by 82 credits. In order to fulfill the credits set need to be arranged local content to meet the shortage of credits from the core curriculum that is suitable for learning access. Purpose: Obtain the amount of data on the number of laboratory tests and local subjects. Method: Secondary Data from the recording and reporting of each laboratory for 3 months. Results: A total of 48.04% clinical chemical test types. A total of 18.87% hematological examination. A total of 1.88% of parasitological and microbiological examination. A total of 19.54% of immunological examination. The curriculum that is used by the Poltekkes Department of Health analyst Semarang 108 SKS with 82 SKS core curriculum and 26 SKS local payload. The subject or number of face-to-face is based on the data proportion of three large groups of tests, namely clinical chemistry (48.04%). Immunological examination (19.54%) and hematological examination (18.87%). Conclusion: The most proportion of tests on fasyankes are clinical chemistry (48.04%). Courses "Knowledge of materials practice" could be added to the curriculum of the D3 of the Poltekkes health analyst Program in Semarang. Suggestion: Need to calculate the credits and proportion of face to face or depth to the local content course "knowledge of practice materials" and placement in the semester.